Empowerment of PKK Mothers in Caring for Hair through Teaching Videos of Traditional Hair Care - Jubaedah, Lilis; Arum, Aniesa Puspa (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2021)
Empowerment of PKK Mothers in Caring for Hair through Teaching Videos of Traditional Hair Care. The objectives of this Community Service are 1) Increase the motivation of PKK mothers to bring out creativity in doing traditional hair care. 2) Improve the skills of PKK mothers to be creative and innovative in doing traditional hair care with the right techniques during the Covid 19 pandemic. 3) Providing knowledge about effectiveness in entrepreneurship. The method used is presentation and discussion by holding make-up webinars through zoom meetings. The webinar activity in August 2020 was attended by 20 participants from Jaka Sampurna Village, Bekasi. The activities included training in hair care competency skills by showing learning videos for traditional hair care. The results of this community service program are (1) partners have knowledge of traditional hair care. (2) partners can apply special skills in the field of hair care in their family and surrounding communities. (3) partner's interest in developing skills by opening a business in the hair sector.